Analisis Segmenting, Targeting, dan Positioning Bank Maybank Indonesia Dalam Membangun Citra Lifestyle Banking - Achmad Axsel Fahrezi; Sophia Rani Larasati; Ida Ayu Nuh Kartini (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The increasingly competitive banking industry encourages financial service institutions to market their products by emphasizing brand image and customer experience. Therefore, this study aims to analyze Maybank Indonesia's positioning in building its lifestyle banking brand using the Segmentation, Targeting, and Positioning (STP) approach. This research employed a qualitative descriptive method using secondary data obtained from the company's website, digital promotional media, and various publications related to Maybank Indonesia's services. The findings indicate that Maybank Indonesia conducts market segmentation based on lifestyle dimensions, financial needs, and levels of economic activity. These segments primarily target professionals, entrepreneurs, and modern consumers with lifestyle-oriented preferences. Through the lifestyle banking concept, Maybank has transformed its banking marketing approach from a transactional orientation to one based on relationships and customer experiences. This positioning strategy contributes to strengthening the company's brand identity and fostering emotional connections with customers through services that align with their lifestyles.